Implementation of Basel III accords in Mutual Trust Bank: risk based capital adequacy ratios requirement of Bangladesh Bank - Mustary, Tahrima (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.